The Impact of Quiziz-Assisted Quantum Learning on Students' Learning Outcomes and Creativity - Siti Jannatul Ainiyah, Nuril Huda, Sunardjo (Journal of Educational Studies, 2025)
Digital apps like Quizizz are becoming more and more popular in the Quantum Learning method as a result of the fast development of technology in the field of education. But how much of an effect Quiziz-Assisted Quantum Learning can have on boosting students' creative capacities and learning results is still up for debate. In this study, we'll look at how the quantum learning paradigm, with the help of Quizizz, affected the creativity and learning results of SMAN 1 Bangkalan 11th graders. Researchers at SMAN 1 Bangkalan used a quasi-experimental design with a one-group pretest-posttest type to find out how much of an impact quantum learning using Quizizz has on students' creativity and learning results. The MANOVA test, which incorporates the results of the validity, reliability, normalcy, and homogeneity tests of the instruments, is used to analyse the data and find the response to the study hypothesis. The hypothesis test findings demonstrate that the significance level is less than 0.05, with a value of 0.000. The hypothesis test findings show that Quiziz-Assisted Quantum Learning has an effect on the learning outcomes and creativity of SMAN 1 Bangkalan students.